(untitled) (American Journal of Islam and Society, 2011)
Political Islam, Iran, and the Enlightenment is Mirsepassi’s latest treatise that focuses on the Iranian intellectual and political climate. Mirsepassi is concerned to show the German and French intellectual influences of Islamist intellectuals as they search for an appropriate response to modernity. With Iran taken as a case study, Mirsepassi’s discussion is intended to undermine those analyses of Muslim political aspirations which deem these aspirations to be inherently anti-Western. Comprising an introduction and seven chapters, Mirsepassi’s work speaks to those researchers in a range of sociopolitical disciplines concerned with coming to grips with intellectual developments in the Muslim world. The book might also interest those interested in understanding the impact of continental philosophy on the Muslim world. Although the emphasis is on Iran, an attempt is made in the final chapter, especially, to broaden the discussion by dealing with the Indian experience of modernity. According to Mirsepassi, the Muslim understanding of modernity and secularism was influenced by the specific visions of modern society held by Kemal Ataturk and the “Shah of Iran” (presumably the ambitious Reza Shah). These two figures were in turn influenced by the antireligious fervor of French secularism. The attempt of Muslim intellectuals, therefore, to establish a correct vision of society was informed by the radical Counter- Enlightenment figures of German and French philosophy. Furthermore, Muslim intellectuals overlooked Western visions of modern society which were not antireligious. Political Islam, Iran, and the Enlightenment, therefore, constructs a narrative that leads to examining the experience of British- style secularism in India. Mirsepassi’s fear is that a lack of appreciation of the European heritage of Islamists ‒ who Mirsepassi sees as intellectually and politically totalitarian and as representing all Muslims ‒ will lead to the sidelining of two groups from within the Muslim world. These two groups are the quietist ulama and the reformist intellectuals, the latter of which offer Mirsepassi the hope of an Islamic response to modernity that is consistent with democratic principles ...